Si Bule Masuk Islam: Western Converts to Islam in Indonesia - more than just Converts of Convenience? - Brice, M. A. Kevin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
In discussing converts to Islam, two different types of converts are often identified based on the reason for conversion: converts of convenience and converts of conviction. The common view is that in most (if not all) cases, conversion to Islam in Indonesia by Westerners is about facilitating marriage and so the converts should be classified as converts of convenience. Evidence of the commonality of this view is considered by reference to advice offered to Westerners about marriage to Indonesians on specialist web sites and examples of coverage of the topic in Indonesian social media. By considering a number of brief case studies, the common view is challenged. The binary of “convert of convenience” versus “convert of conviction” is revisited to suggest that individuals may move between the types over a period of time. Finally the paper will consider whether there is anything about Islam in Indonesia which contributes to the phenomenon of “transnational” conversion by Westerners in Indonesia.DOI: 10.15408/sdi.v22i1.1386